DENTAL ANXIETY AMONG ADOLESCENTS-AN OVERVIEW - Alice Murariu; Roxana Vasluianu; Livia Bobu; Raluca Baciu; Simona Stoleriu; Teona Petcu; Gabriela Gelețu (Romanian Society of Oral Rehabilitation, 2022)
Dental anxiety is a phrase used to describe the fear or stress determined by dental treatments. This narrative review aims to highlight some epidemiologic aspects of the phenomenon while searching medical databases for researches relating to the topic of dental anxiety in adolescents. Adolescence represents a period of transition illustrated by changes both at physical level and behavior and personality levels. Anxiety disorders are frequent at this age and they may affect school performance, the relationships with one's family and friends. Dental anxiety is associated with certain trigger factors such as needles or sometimes the simple sight of the dental instruments. Although most patients have a low level of dental anxiety, literature mentions the percentage of 11% for the prevalence of severe dental anxiety and 90% for low anxiety. Most studies show that the female patients are more anxious than the male patients. Among the dental procedures, the ones involving oral surgery, including tooth extraction and local anesthesia, remain the most incriminated trigger factors. This paper also presents the most known questionnaires used in current practice that help the dentist identify anxious patients as well as the etiology of this phenomenon.